(untitled) (Web of Teachers: Inderscience Research, 2025)
Textbooks are a cornerstone of the educational process in Uzbekistan, providing the primary learning resources for students across all grade levels. However, the state of textbooks in Uzbekistan’s general education schools faces several challenges that hinder the effectiveness of education. These challenges include outdated content, poor quality, limited accessibility, unequal distribution, and high costs. This article explores these issues in detail and provides proposed solutions, including the regular updating of textbooks, improvements in printing quality, equitable distribution across the country, and the introduction of digital textbooks. The article argues that through systematic reforms, Uzbekistan can enhance the quality of its education system and ensure that textbooks contribute effectively to the development of critical thinking, creativity, and academic excellence among students.